If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 12f = 24 Solving 2 + 12f = 24 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 12f = 24 + -2 Combine like terms: 2 + -2 = 0 0 + 12f = 24 + -2 12f = 24 + -2 Combine like terms: 24 + -2 = 22 12f = 22 Divide each side by '12'. f = 1.833333333 Simplifying f = 1.833333333
| 5x-3=4-3x | | 0.3(5)+5.35=y | | 41.6=r+9.2 | | 0.3(3)+5.35=y | | 2+9f=18 | | 2+6f=18 | | 3+6f=18 | | 3+5f=15 | | 33*17= | | 0.3(1)+5.35=y | | x=-6/2/3 | | 40x+5000=6400 | | 9x-3(2x-4)-5=25 | | 16=e+1.1 | | (2x-8)(x+5)= | | 40(300)+5000=y | | 3.2=s+1.1 | | 40(200)+5000=y | | x+7/8=-1/2 | | 5+n=22.2 | | 40(100)+5000=y | | 6+2/3x | | 51/5+v=10 | | 1380=x^2(.16x+58) | | 10.2=x+2 | | 3x^2-3=-78 | | 3x^2-3=78 | | 45+1y=0 | | 72=12+k | | 1/2(-2)+3=y | | (6x/x^2-6)=-6/5 | | ln(5x+8)-ln(x)=ln(6) |